Southeast Asian women in K-12 educational leadership positions - Phannaphob, Chai. University High School, Fresno, CA; Phannaphob, Chai; Phannaphob, Chai (Center for Leadership Equity and Research)
The number of Southeast Asian women in the field of K-12 educational leadership positions in Californias Central Valley is a current topic that deserves academic attention. Data documenting the success of Southeast Asian female K-12 school administrators is difficult to find because Southeast Asian women working in K-12 school administration is a recent demographic and no such study currently exists. This study focuses on the challenges of gender, ethnicity, and the leadership styles of Southeast Asian women in K-12 administration and teacher-leader positions. The role of a school leader is challenging, overwhelming, and stressful. Despite the perceived undesirable responsibilities of the job, some Southeast Asian women are motivated to pursue positions of K-12 educational leadership. Present trends of hiring and recruiting diversity in education have widened the pool of potential school leaders. The purpose of this project is to explore the challenges and discover the ways that Southeast Asian women have been able to overcome obstacles in K-12 school administration.